2002
DOI: 10.1074/jbc.m204121200
|View full text |Cite
|
Sign up to set email alerts
|

m-Bop, a Repressor Protein Essential for Cardiogenesis, Interacts with skNAC, a Heart- and Muscle-specific Transcription Factor

Abstract: The m-Bop protein encoded by the mouse Bop gene is strongly expressed in heart and skeletal muscle, and recent studies with Bop knockout mice have demonstrated that m-Bop is essential for cardiogenesis in vivo and can act as a HDAC-dependent repressor in vitro. In the present studies, m-Bop was observed to interact with skNAC, a reported transcriptional activator specific to heart and skeletal muscle. The amino-terminal S region of the split S-ET domain of m-Bop as well as the MYND domain were required for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(129 citation statements)
references
References 23 publications
7
121
0
Order By: Relevance
“…BS69 and m-Bop have been shown to interact with a conserved binding motif, PXLXP, in cellular and oncoviral proteins, an interaction that is dependent on the MYND domain (38,(43)(44)(45). Consistent with these observations, ETO NHR3/4 binds a motif with a PPLXP pattern in N-CoR (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…BS69 and m-Bop have been shown to interact with a conserved binding motif, PXLXP, in cellular and oncoviral proteins, an interaction that is dependent on the MYND domain (38,(43)(44)(45). Consistent with these observations, ETO NHR3/4 binds a motif with a PPLXP pattern in N-CoR (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…The MYND-type zinc fingers resident in NHR4 of ETO have also been identified in other co-repressor proteins, notably human BS69, the skeletal and heart muscle specific m-Bop (mouse CD8b opposite) protein in mice, the Caenorhabditis elegans proteins BRA-1 and BRA-2, and the Myc-related cellular protein MGA (38,43). BS69 and m-Bop have been shown to interact with a conserved binding motif, PXLXP, in cellular and oncoviral proteins, an interaction that is dependent on the MYND domain (38,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings demonstrate that SETD3 exerts specific HMTase activity in the mono-and dimethylation of H3K4 and H3K36 under both in vitro and in vivo conditions. SETD3 Induces Transcriptional Activation-It was noted previously that histone H3K4 HMTase SMYD1 functions as a transcription activator, playing an essential role in myogenesis and cardiogenesis in different species (6,(25)(26)(27). To determine whether or not methylation of H3K4 and H3K36 by SETD3 can be attributed to a general transcription activation effect similar to that of SMYD1, we conducted a transient transfection assay using the CMX-GAL4-SV40 reporter system.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a function for skNAC in transcription regulation has also been suggested by Sims and colleagues (Sims et al, 2002); the authors showed for the first time that skNAC binds to the m-Bop/Smyd1 protein [note, muscle (m)-Bop is the isoform of the the Smyd1 gene that is expressed in muscles], a SET-domaincontaining histone methyltransferase that also contains a MYND domain known to be involved in the recruitment of histone deacetylases (HDACs). Interestingly, the skNAC-Smyd1 complex localizes to the nucleus in myoblasts at an early differentiation stage and then translocates to the cytosol at later stages of differentiation, where at least Smyd1 is associated with sarcomeric structures (Just et al, 2011;Li et al, 2011), suggesting that, besides regulating transcription, the proteins might also exert a function in the cytoplasm at later stages of myogenesis.…”
Section: Introductionmentioning
confidence: 99%